Bibliometric Analysis of Critical Thinking Skills and Growth Mindset through Project-Based Learning - Efendi, Meri; Sunyono; Suyatna, Agus (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
Significant changes in contemporary education require instructional approaches that can effectively foster critical thinking skills and a growth mindset, particularly among Generation Z learners. Project-Based Learning (PjBL) has been widely recognized as a student-centered pedagogical model that promotes active engagement, problem-solving, and higher-order thinking. This study aims to examine research trends related to the implementation of PjBL in developing students’ critical thinking skills and growth mindset through a bibliometric analysis. Data were collected from relevant scholarly publications and analyzed using VOSviewer to visualize research patterns and thematic relationships. The findings indicate that PjBL is strongly associated with the development of critical thinking skills, while its connection with growth mindset remains comparatively underexplored. These results highlight a research gap in the integration of cognitive and motivational constructs within PjBL studies and suggest directions for future research to strengthen the pedagogical impact of project-based learning in 21st-century education. Further studies are needed to explore how PjBL can be effectively designed to promote both cognitive skills and a growth mindset simultaneously. Bridging this gap will provide valuable insights for educators seeking to maximize the potential of PjBL in fostering holistic student development.